Association Between Parental Knowledge and Compliance with Complete Basic Immunization Among Children Under Five - Samila; Kurniawati (PT. Nasyah Medika Care, 2024)
Background: Complete basic immunization is one of the most effective public health interventions for preventing vaccine-preventable diseases among children under five. However, parental compliance with the recommended immunization schedule remains a challenge, particularly due to differences in parents' knowledge regarding childhood immunization. Identifying the association between parental knowledge and immunization compliance is essential for developing effective health education and immunization promotion strategies. Research Objective: This study aimed to determine the association between parental knowledge and compliance with complete basic immunization among children under five in the working area of Antang Primary Health Center, Makassar, Indonesia. Methods: This analytical observational study employed a cross-sectional design. A total of 31 parents of children under five were recruited using a total sampling technique. Parental knowledge was assessed using a structured questionnaire, while compliance with complete basic immunization was verified through the Maternal and Child Health Handbook and immunization records. Data were analyzed using descriptive statistics and the Chi-square test with a significance level of p < 0.05. Results: Most respondents had good knowledge regarding complete basic immunization (58.1%), while 74.2% complied with the recommended immunization schedule. Bivariate analysis revealed a statistically significant association between parental knowledge and compliance with complete basic immunization (p = 0.006). Parents with good knowledge demonstrated a higher level of compliance with the national immunization schedule than those with moderate or poor knowledge. Conclusion: Parental knowledge was significantly associated with compliance with complete basic immunization among children under five. Strengthening health education and family-centered health promotion programs at primary healthcare facilities is essential to improve parental knowledge, increase immunization coverage, and reduce the incidence of vaccine-preventable diseases among children